Resistência ao desgaste por fricção cíclica de ligas Al-Cu-Cr com diferentes teores de Cu e Cr solidificadas unidirecionalmente - Lantmann, Rafael Vieira (2023)
Aluminum alloys containing transition metal alloying elements have attracted interest from researchers. The effect of Cr additions of 0.25 and 0.50% on the thermal profile, micro-structure, hardness, and linear reciprocating sliding wear response of as-cast hypoeutectic Al-Cu alloys with 2.5; 3.5; 4.5% Cu (wt.%) was investigated. The binary Al-Cu and ternary Al-Cu-Cr alloys were directionally solidified under upward nonsteady state heat transfer conditions using a dedicated solidification apparatus. Thermal analysis based on differential thermal analysis (DTA) and cooling curve profiles was performed to determine solidification thermal parameters such as Liquidus temperature (ṪL), transformation enthalpy (H), and liquid cooling rate (ṪL). Samples extracted from the solidified ingots were submitted to optical microscopy, hardness measurement and linear reciprocating sliding wear test using a high-frequency reciprocating rig (HFRR). The results showed a decrease at the beginning of solidification (ṪL) and of the transformation enthalpy (H) when both alloy Cu and Cr contents increased, with a higher influence of Cu. The addition of Cu decreased cooling rates, whereas the increase in the alloy Cr concentration showed an opposite behavior, increasing cooling rates. The refinement of the primary dendrite arm spacing (λ1), as a consequence of the increase in alloying elements and solidification cooling rates, enhanced the hardness of the alloys, with the maximum value of 58 HB in the ternary Al-4.5Cu-0.50Cr alloy. The wear tests indicated a better response to wear associated with microstructure re-finement for the alloys with 2.5% Cu, for both Cr contents, na almost constant behavior for the 3.5% Cu alloys, and an opposite performance for the alloys with 4.5% Cu alloys that showed better wear resistance with coarsening of the λ1 and with the increase in the amount of the eutectic micro-constituent.